Middle Subtalar Joint Facet Subluxation as a Marker of Collapsing Flatfoot Deformity: A Case-Control Study. Issue 4 (16th October 2019) - de Cesar Netto, Cesar; Godoy-Santos, Alexandre Leme; Roberts, Lauren; Saito, Guilherme Honda; Lintz, Francois; Siegler, Sorin; Greditzer, Harry; Sofka, Carolyn; Deland, Jonathan; Ellis, Scott
Category: Hindfoot Introduction/Purpose: Peritalar subluxation comprises part of the three-dimensional and complex distortion that occurs in patients with adult-acquired flatfoot deformity (AAFD) and is characterized by subluxation of the hindfoot through the triple joint complex. It is traditionally graded on weightbearing computed tomography (WBCT) coronal plane images, depending upon the degree of angulation and subluxation of the posterior facet of the subtalar joint. In this case-control study, we describe a new marker of peritalar subluxation represented by the amount of subluxation and joint incongruence of the middle facet of the subtalar joint. We hypothesized that the amount of joint subluxation and incongruence at the middle facet would be significantly increased in patients with AAFD when compared to controls. Methods: Case-control study, we included 30 patients with stage II AAFD (19 females/11 males), mean age 52.2 (range, 29 to 81) years, and 30 controls (18 females/12 males), mean age 49.3 (range, 28 to 83) years, that underwent WBCT as part of the evaluation of their foot condition. Age and gender were statistically similar in both groups. The amount of subluxation of the subtalar joint at the middle facet (% of uncoverage) and angle of joint incongruence, both measured at the midpoint of its longitudinal length, was measured in coronal WB CBCT images by two independent and blinded fellowship-trained foot and ankle surgeons. A second set of measurements was performed after one month (wash-out period). Intra- and interobserver reliability were assessed by Pearson/Spearman's and Intraclass Correlation Coefficient (ICC), respectively. Comparison was performed using Paired Student T-Test or each pair Wilcoxon rank sum test. P-values lower than 0.05 were considered significant. Results: We found overall good to excellent intra- (range, 0.90-0.95) and interobserver reliability (range, 0.75-0.93) for the measurements. We found significantly increased subluxation of the subtalar joint at the middle facet in patients with AAFD, with a mean value for middle facet uncoverage of 45.3% (95% CI, 40.5% to 50.1%), when compared to 4.8% (95% CI, 0% to 9.6%) in controls (p<0.0001). Significant differences were also found for middle facet subtalar joint incongruence angle, with a mean value of 17.3 degrees (95% CI, 15.5 to 19.1) in AAFD patients and 0.3 degrees (95% CI, -1.5 to 2.1) in controls (p<0.0001). Conclusion: We described the use of the subtalar joint middle facet as a marker for peritalar subluxation in patients with AAFD. We found significant and marked differences in the percentage of joint uncoverage and incongruence when compared to controls. Hopefully, the use of the middle facet as an indicator for peritalar subluxation can potentially help in the early detection of high- risk AAFD patients for progressive collapse and development of sinus tarsi and subfibular impingement, as well as arthritic degeneration of the subtalar joint. Future longitudinal and prospective studies are needed.